Assessment of Salivary Flow Rate and Salivary PH in Subjects with Smoked, Smokeless, and Combined form of Tobacco Habits (Epidemiological-Based Study) - Sethi, Kavleen K.; Srivastava, Sunita; Sinha, Abhishek; Mishra, Anuj; Iqbal, Haider; Srivastava, Tanmay (Indian journal of community medicine, 2025)
Background: Saliva is a complicated secretion of the oral cavity and is the first fluid to be exposed to the toxic components of tobacco products. Saliva undergoes structural and functional changes due to tobacco use throughout time. As a result, measurements of salivary flow rate (SFR) and pH were made in subjects with habit of smokeless, smoked, and combined forms of tobacco habits. Methodology: The study was conducted in a dental institute. Subjects with the habit of smoking, smokeless, and combined forms of habits were included in this study. Schirmer tear strips and pH strips were used to assess SFR and pH. Results: On comparison of SFR between control and habit groups, a statistically significant reduction of SFR was observed in habit groups. On comparison of salivary pH, a statistically significant decrease was observed in smokeless and smoked form of tobacco usage group when compared with the control group. Duration, frequency, and exposure also alter SFR and pH. Significant gradual decline in resting salivary flow rate levels with increase in duration of tobacco usage and increase in number of packs consumed/day was observed. Conclusion: The role of salivary flow and pH is to maintain oral and dental health. Based on the results of this study, we concluded that long-term habits, whether smokeless, smoking, or combined tobacco habit, significantly reduce SFR and pH. These alterations can render oral mucosa more vulnerable to various oral diseases.